Non-Markovian Transfer Tensor Method Used in a Chemical Reaction in Liquids (Journal of Atomic and Molecular Sciences, 2016)
In this paper, the non-Markovian transfer tensor method (TTM) suggestedby Cao's group was utilized in a real chemical reaction in liquids from a classicalpoint of view. From the results of this numerical simulation, dramatic enhancementin speed of calculations and decrease in computational cost are shown by applyingTTM method. It is wise to be used in complex systems with lots of degrees, such asthe process of protein folding or in treating propagations with mountains of data. Forsome specific quantities we are interested in, how to find a map from complex systemsto simple ones and from huge freedoms to a few ones, such as just to one freedom inthis paper, it remains something for us to do in the future.